Construction of a continuous radar field of a hydrometeorological monitoring system based on a geometric approach - Perelygin, B.V.; Luzbin, A.M. (Radiotekhnika, 2017)
The concept of a continuous radar field generated by a system of meteorological radars is considered. To accommodate meteorological radars, it is proposed to apply a geometric approach, which consists in arranging meteorological radar stations at the vertices of various polygons and which greatly simplifies the construction of the required radar field. Quantitative indicators for estimating the quality of the radar field and the results of their calculations for various variants of constructing the radar field are proposed.